Problemy zarządzania przedsiębiorstwem w warunkach globalizacji - Sobotkiewicz, Dariusz (Problems of Enterprise Management in Globalization's Terms, 2006)
The article presents an attempt to prove, that in terms of regionalization, globalization and integration, multinational enterprises incline for introduction of centralized management 's system, which appoints the role, which foreign subsidiaries have to play on the market. This issue is favorable to limit entrepreneurship of staff, which manages these subjects and at the same time gives measurable benefits for the whole organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 340-348